The features of mobile app design model from Dyscalculia children personal factor - Mohd Ariffin, Mazeyanti; Abd Halim, Fiqa Azureen; Sugathan, Savita K. (2018)
Learning disabilities (LD) is a term that describes specific kinds of learning problem. LD affects how the people understand, remember and respond to information.The most common LD are including Dyslexia, Dyscalculia and Dysgraphia. Dyslexia is difficulties in reading, Dyscalculia refer to difficulties in math and Dysgraphia is difficulties in writing.Nowadays, mobile learning is widely used in special educational practice.Hence, Dyscalculia children should utilize the mobile or tablet devices as supportive learning tools to support their learning.However, currently there are inadequate studies on mobile app design model for mobile app designers and developers in designing and developing mobile app for Dyscalculia children.Thus, the aim of this study is to develop mobile app design model called Calculic Model that includes 3 factors which are personal, instructional and environment.The purpose of this paper is to report on the features under personal factor that relates to the cognitive of Dyscalculia children. The interview sessions were conducted with Dyscalculia practitioners involving teachers, pediatric and educational psychology.This has resulted in identifying the features of each component under the personal factor.Later the development of the Calculic Model will be based on the components and features that have been identified through interview session.